Near-Simultaneous Development of Coronary and Pulmonary Thrombosis in a Patient With COVID-19 - John-Henry L. Dean; Mayank P. Patel; William T. Williams; Michael N. Moulton; Michael S. Cahil; Bryan C. Ramsey (Annals of Internal Medicine: Clinical Cases)
Venous thromboembolism and in situ thrombosis are recognized complications of SARS-CoV-2 infection and are associated with adverse outcomes. The development of multiple thrombotic events in patients with COVID-19 has been reported, although the combination of venous and arterial thrombotic events is rarely recognized. Here, we describe a 42-year-old man without significant risk factors for cardiovascular disease who developed a segmental pulmonary thrombus and coronary thrombus within hours while hospitalized for the treatment of nonsevere COVID-19 pneumonia.